(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
For almost all ethnic communities in NE India, dried fish is an integral part of food, and because of its ubiquity, ethnic individuals dry fish by various methods and protect it for longer periods of time. As the educational level of the general population in rural areas rises, consumers are currently more concerned about the health benefits of nutritious products. Quality management of such an essential food is therefore compulsory, triggering the justification for the investigation. The important type of food product is known to be dried fish, an exceptional wellspring of animal protein. Safeguarding and handling of dried fish is highly important due to its extremely perishable nature. Smoking or sun-drying fish are ancient survival methods. Due to spoilage, invasion of flies or other form of bacterial contamination of the protected fish causes health hazards. As different microorganisms contaminate the dried fish right from catching to selling the items, microbiological analysis is also a very important aspect of the research. Thus, 16s r-RNA area amplification and detection is now gaining momentum days after isolation of bacteria from various dried fish samples.